Equity, Equality and Diversity in the Nordic Model of Education 2020
DOI: 10.1007/978-3-030-61648-9_14
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Parents’ Own Reading for 10-Year Old Students’ Reading Achievement in the Nordic Countries

Abstract: The Nordic education model of an inclusive school for all aims at giving children equal, and excellent, opportunities for acquiring high levels of reading ability. It is well documented that both students’ and their parents’ reading interest is closely and positively associated with students’ reading achievement. There is therefore cause for concern when reading interests seem to be in decline both among parents and among today’s students. Family socio-economic background is also well known to relate strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Studies have found many factors affecting students' reading skills and attitudes. Typically, the supportiveness of the home environment (Gustafsson et al, 2013;Hemmerechts et al, 2017;Mullis et al, 2017, Home Environment Support section), socioeconomic background (Hemmerechts et al, 2017;Neff, 2015;Sirin, 2005;Støle et al, 2020), and engagement in reading (Ho & Lau, 2018;Wantchekon & Kim, 2019) are found to be important explanators of reading proficiency. Gender issues also arise regularly in literacy studies since gender difference in large-scale studies has for years favored girls (Gustafsson et al, 2013;OECD, 2019b, 141-149).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found many factors affecting students' reading skills and attitudes. Typically, the supportiveness of the home environment (Gustafsson et al, 2013;Hemmerechts et al, 2017;Mullis et al, 2017, Home Environment Support section), socioeconomic background (Hemmerechts et al, 2017;Neff, 2015;Sirin, 2005;Støle et al, 2020), and engagement in reading (Ho & Lau, 2018;Wantchekon & Kim, 2019) are found to be important explanators of reading proficiency. Gender issues also arise regularly in literacy studies since gender difference in large-scale studies has for years favored girls (Gustafsson et al, 2013;OECD, 2019b, 141-149).…”
Section: Introductionmentioning
confidence: 99%